DEVELOPMENT OF METHODOLOGY TO DETERMINE THE DURATION OF HEATING OF THE CARGO IN CONVECTIVE GARAGES DEFROST - Parunakjan, V. E.; Dzhenchako, V. Gh. (Science and Transport Progress, 2006)
The process of warming-up of a frozen load has been considered. A method is developed to determine duration of the warming-up process depending on the size of the frozen layer.